DODAB: monoolein-based lipoplexes as non-viral vectors for transfection of mammalian cells - Silva, J. P. Neves (2011)
DNA/Cationic liposome complexes (lipoplexes) have been widely used as non-viral vectors for transfection. Neutral lipids in liposomal formulation are determinant for transfection efficiency using these vectors. In this work, we studied the potential of monoolein (MO) as helper lipid for cellular transfection. Lipoplexes composed of pDNA and dioctadecyldimethylammonium bromide (DODAB)/1-monooleoyl-rac-glycerol (MO) at different molar ratios (4:1, 2:1 and 1:1) and at different cationic lipid/DNA ratios were investigated. The physicochemical properties of the lipoplexes (size, charge and structure), were studied by Dynamic Light Scattering (DLS), Zeta Potential (æ) and cryo-transmission electron microscopy (cryo-TEM). The effect of MO on pDNA condensation and the effect of heparin and heparan sulphate on the percentage of pDNA release from the lipoplexes were also studied by Ethidium Bromide (EtBr) exclusion assays and electrophoresis. Cytotoxicity and transfection efficiency of these lipoplexes were evaluated using 293 T cells and compared with the golden standard helper lipids 1,2-dioleoyl-sn-glycero-3-hosphoethanolamine (DOPE) and cholesterol (Chol) as well as with a commercial transfection agent (Lipofectamine™LTX). The internalization of transfected fluorescently-labeled pDNA was also visualized using the same cell line. The results demonstrate that the presence of MO not only increases pDNA compactation efficiency, but also affects the physicochemical properties of the lipoplexes, which can interfere with lipoplex-cell interactions. The DODAB:MO formulations tested showed little toxicity and successfully mediated in vitro cell transfection. These results were supported by fluorescence microscopy studies, which illustrated that lipoplexes were able to access the cytosol and deliver pDNA to the nucleus. DODAB:MO-based lipoplexes were thus validated as nontoxic, efficient lipofection vectors for genetic modification of mammalian cells. Understanding the relation between structure and activity of MO-based lipoplexes will further strengthen the development of these novel delivery systems.